The Effect Of Sentani Airport On Rental Prices For Shophouses - Akhmad Mabarun; Aryanto Dwi Nugroho; Firman Romadhon; Wisdasari Ayu Bintari (CV. Green Publisher Indonesia, 2022)
The Existence of Sentani International Airport is considered as driving factor for the growth of economic activity for the region which will automatically affect the increase in the value of surrounding property. The aims of the study are: (1) explore the effect of airport distance on the rental price of shophouse, (2) explore the effect of the road width on the rental price, (3) explore the effect of the shophouse building size on the rental price, (4) explore the effect of the shophouse building frontage on the rental price. This analysis used a multiple linear regression. The result of this analysis conclude that the variable distance from the airport has significant effect of rental price 110.0602,- rupiah per square meter. While the variables of building size, road width, and building frontage have no significant effect on shophouse rental prices.